Plasma endothelin-1 levels in patients with systemic sclerosis: influence of pulmonary or systemic arterial hypertension. Issue 9 (September 1995) - Morelli, S; Ferri, C; Di Francesco, L; Baldoncini, R; Carlesimo, M; Bottoni, U; Properzi, G; Santucci, A
Abstract : OBJECTIVES--To investigate the behaviour of circulating endothelin-1 (ET-1) in patients affected by systemic sclerosis and to elucidate the relationship between systemic and pulmonary plasma peptide and arterial pressure levels. METHODS--Plasma ET-1 concentrations were determined in 48 patients affected by systemic sclerosis (41 women, seven men; mean age 47.2 (SD 5.5) years) with or without systemic or pulmonary hypertension (or both). A group of 18 normal volunteers served as controls (15 women, three men; mean age 45.0 (10.1) years). RESULTS--Plasma ET-1 levels were significantly greater in patients affected by systemic sclerosis (1.65 (0.29) pg/ml) than in controls (0.63 (0.19) pg/ml) (p < 0.0001). Pulmonary artery systolic hypertension alone was present in 14 patients with systemic sclerosis (50.5 (8.49) mm Hg, range 37-67 mm Hg), and systemic hypertension alone (160.7 (5.9)/100.6 (3.2) mm Hg) was present in 11 patients. Both conditions were present in 12 patients, while 11 patients had systemic hypertension. There were no significant differences in plasma ET-1 levels between patients with pulmonary hypertension alone (1.62 (0.21) pg/ml) and those with systemic hypertension alone (1.65 (0.43) pg/ml). In particular, patients with normal pulmonary artery and systemic pressures (n = 11) had plasma ET-1 concentrations identical to those found in patients (n = 12) with both pulmonary and systemic hypertension (1.70 (0.15) v 1.64 (0.35) pg/ml, respectively). No correlations were observed between plasma ET-1 and either pulmonary or systemic pressures. CONCLUSION--Systemic sclerosis is characterised by increased plasma ET-1 levels, but neither pulmonary nor systemic hypertension are accompanied by further increase in plasma peptide levels.